The impact of adjuvant antihormonal therapy versus observation on recurrence of borderline ovarian tumors: A retrospective cohort study - Kelsey C. Goon; Jeanelle Sheeder; Miriam D. Post; Jill Alldredge (Gynecologic Oncology Reports, 2023)
Objectives: Adjuvant management of borderline ovarian tumors (BOT) after surgical diagnosis and staging is not standardized. While many patients undergo observation alone, some providers have introduced the use of adjuvant antihormonal therapy for BOT, extrapolating from studies suggesting improvement in progression-free survival in the low-grade serous ovarian carcinoma population. We hypothesized that adjuvant antihormonal therapy after surgical diagnosis of BOT would improve progression-free survival compared to surveillance alone. Methods: This is a retrospective review of BOT at one academic institution over thirteen years comparing management with antihormonal therapy, including aromatase inhibitors, progestins, and selective estrogen receptor modulators, to surveillance alone. Patients with concurrent malignancy were excluded. Data were abstracted from electronic medical records. Groups were compared by bivariate statistics. Results: We identified 193 patients with BOT. Of these, 17 (8.8%) were treated with adjuvant antihormonal therapy and 24 (12.4%) recurred. Patients treated with antihormonal therapy were more likely to be obese (64.7% vs 37.9%, p = 0.032), have advanced-stage disease (70.6% vs 11.4%, p < 0.001), serous histotype (94.1% vs 59.4%, p = 0.005) or microinvasion (29.4% vs 9.7%, p = 0.030), and less likely to have undergone fertility-sparing surgery (18.8% vs 51.7%, p = 0.012). Use of antihormonal therapy was not associated with a difference in recurrence or survival. Conclusions: This study is the first retrospective cohort review of adjuvant antihormonal therapy in BOT. We found that adjuvant antihormonal therapy for BOT is not associated with recurrence. While this single institution retrospective cohort study may lack the power to confirm or refute benefit, further studies could evaluate whether a subpopulation exists in whom antihormonal therapy is worthwhile.